The idiot box early American television plays - Anniah Gowda, H. H. 1927- (New Delhi Sterling Publishers, 1987)
Discusses some of the plays seen or read by the author during the 1960s.
Keywords: Television plays, American -- History and criticism; American drama -- History and criticism. -- 20th century